Ways of Improving the Competitiveness of Cluster Formations - Oreshkin, Valeriy Alekseevich; Khomutov, Aleksej Olegovich (Российский внешнеэкономический вестник, 2024)
The authors consider trends in the formation of regional clusters and possible ways of their competitiveness increase. Special attention is given to the questions of formation of innovative clusters. Directions of formation of such clasters in various regions of Russia are revealed, possibilities of perfection of this process are shown.